2018
DOI: 10.1097/jom.0000000000001377
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Interrupting Workplace Sitting Time With Non-Exercise Physical Activity

Abstract: Objective:To evaluate the blood pressure (BP) effects of a yearlong e-health solution designed to interrupt prolonged occupational sitting time.Methods:BP data of 228 desk-based employees (45.1 ± 10.5 years) were analyzed at baseline, 3, 6, 9, and 12 months.Results:Systolic BP significantly reduced from baseline for the first 9 months (1.0 to 3.4 mmHg; P < 0.01) while diastolic and mean arterial pressure decreased for the full 12-months (4 to 5 mmHg for diastolic pressure and 3.6 to 4.2 mmHg for MAP; all P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In relation to varied postures, there is evidence that interventions are able to reduce sedentary behaviour and increase physical activity [38]. Furthermore, interrupting the time spent sitting at the workplace might produce long-term reductions in blood pressure [39].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to varied postures, there is evidence that interventions are able to reduce sedentary behaviour and increase physical activity [38]. Furthermore, interrupting the time spent sitting at the workplace might produce long-term reductions in blood pressure [39].…”
Section: Discussionmentioning
confidence: 99%
“…stairwells), restricting elevators usage, active commuting to work and physical activity counselling are some attempts to reduce occupation-related sedentary behavior [ 86 89 ]. Contemporary evidence claims workplace digital interventions such as e-health may influence cardiometabolic disease risk especially mean arterial pressure (MAP) [ 90 , 91 ]. A 12-month e-health intervention was found to reduce MAP (3.6–4.0 mmHg) significantly compared to baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In the chronic studies, only one study reported the adherence to the intervention [52], so in the other studies it is not known how much of the intervention was completed by the participants. Also, even though most of the interventions in the chronic studies were similar, they were not standardized, along with the fact that four studies had no control group [49,51,53,56] to make direct comparisons to the interventions. The average quality score could also be a limitation, with both the acute and chronic studies averaging 7 points, indicating average quality.…”
Section: Discussionmentioning
confidence: 99%